Forms and teaching methods in the system of continuing professional education - Sundeeva, Ludmila A. (2020)
The search for innovative forms and teaching methods is highly significant in the context of continuing education, since the competitiveness of modern teachers depends on the quality of the continuing education process. The purpose of the article is to analyze the experience of using innovative forms and methods in the system of advanced training and professional retraining of students. The article presents the experience of organizing the work of students using modern forms and methods of advanced training. The implementation of video conferencing allows students to learn advanced professional experience, exchange relevant information, ask leading experts questions of interest and receive recommendations. Training activities contribute to the intensification of the learning process. It is aimed both at mastering the cognitive component of the information transmitted by the teacher, and the formation of new professional models of behavior that meet modern requirements for the implementation of pedagogical activity. Mental maps are a means of logical structuring of information and are aimed at its operational development. Project activities allow students to build professional competence, find new innovative ways to solve problems, assess the feasibility and effectiveness of project ideas.